Analisis Pemahaman Konsep Pembagian pada Siswa Kelas III Sekolah Dasar - Shindi Oksaria; Salmaini Safitri Syam; Chandra Chandra (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to analyze the level of understanding of the division concept among third-grade elementary school students. Understanding division is a fundamental component in mathematics learning, serving as a basis for more complex numerical operations in higher grades. The research employed a descriptive qualitative method involving 5 students from an elementary school in. Data were collected through diagnostic tests, interviews, and observations. The findings revealed that most students still struggle to grasp the concept of division, particularly in understanding it as a grouping process and as repeated subtraction. Factors influencing students' comprehension include limited use of varied teaching methods, insufficient application of concrete learning media, and differences in students' learning styles. These findings are expected to serve as a reference for teachers in designing more effective and contextual learning strategies to enhance students’ understanding of the division concept at the elementary level.